PERAN DAN IMPLEMENTASI HUKUM DALAM MEMBERIKAN KEPASTIAN JAMINAN SOSIAL BAGI PEKERJA SEKTOR INFORMAL - Wandi Subroto (GoAcademica Research dan Publishing, 2019)
The purpose of this study is to analyze the role and implementation of the law in providing social security certainty for informal sector workers. This study uses a juridical-normative method. The types of legal sources used in this study are secondary sources of law which are discussed using a sociological perspective. The analysis and writing was done by qualitative method. Data was collected through interview techniques, giving questionnaires, and literature studies. The number of respondents in this study were 50 people who worked in the informal sector in the city of Palembang. The selection of respondents was done by purposive sampling technique. Based on the analysis of legal materials and sociological analysis, it can be concluded that the law protects social welfare through Law no. 40 of 2004 states that the National Social Security System adheres to the principle of compulsory participation for all residents in Indonesia. In the implementation of this policy, the informal sector is still experiencing several obstacles, including educational factors, economic factors and institutional factors so that the level of worker participation tends to be minimal and there is no equal distribution.